The Thalamus as a Blackboard for Perception and Planning - Worden, Robert; Bennett, Max S.; Neacsu, Victorita (Frontiers in Behavioral Neuroscience, 2021)
It has been suggested that the thalamus acts as a blackboard, on which the computations of different cortical modules are composed, coordinated and integrated. This paper asks what blackboard role the thalamus might play, and whether that role is consistent with the neuroanatomy of the thalamus. It does so in a context of Bayesian belief updating, expressed as a Free Energy Principle. We suggest that the thalamus-as-a-blackboard offers important questions for research in spatial cognition. Several prominent features of the thalamus – including its lack of olfactory relay function, its lack of internal excitatory connections, its regular and conserved shape, its inhibitory interneurons, triadic synapses, and diffuse cortical connectivity – are consistent with a blackboard role. Different thalamic nuclei may play different blackboard roles: (1) The Pulvinar, through its reciprocal connections to posterior cortical regions, coordinates perceptual inference about ‘what is where’ from multi-sensory data. (2) The Mediodorsal nucleus, through its connections to prefrontal cortex, and the other thalamic nuclei linked to the motor cortex, uses the same generative model for planning and learning novel spatial movements. (3) The paraventricular nucleus may compute risk-reward trade-offs. We also propose that as any new movement is practiced a few times, cortico-thalamo-cortical links entrain the corresponding cortico-cortical links, through a process akin to supervised learning. Subsequently, the movement becomes a fast unconscious habit, not requiring the MD nucleus or other thalamic nuclei, and bypassing the thalamic bottleneck.